Rethinking the Jurisdiction of the International Criminal Court: A Move towards Universality (African Journal of Law and Politics, 2023)
The continuous perpetration of international crimes and other crimes of similar nature with disastrous effects on humanity can be attributed to the limits on the jurisdiction of the ICC in prosecuting and sanctioning perpetrators. The Court’s jurisdiction is limited to member states of the Rome Statute, states that accept the jurisdiction of the court on an ad hoc basis and those that have been referred to the court by the United Nations Security council, thus making its jurisdiction to be treaty based (treaty based universal jurisdiction). This paper therefore advocates for an extensive universal jurisdiction for the ICC so as to enable the court prosecute and sanction perpetrators of international crimes without regard to nationality of the perpetrator and place of commission. This is because it is the favourite technic used to prevent impunity for international crimes and one of the most effective methods to deter and prevent international crimes by increasing the likelihood of prosecution and punishment of its perpetrators.